2020
DOI: 10.1177/0306419020915725
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive apprenticeship and T-shaped instructional design in computational fluid mechanics: Student perspectives on learning

Abstract: The goal of the present work was to explore student perspectives about a course module designed with cognitivist and constructivist learning theories, the cognitive apprenticeship instructional model, and a T-shaped design, specifically the first module of a Computational Fluid Mechanics curricular unit within a Master of Computational Mechanics program. This module was redesigned accordingly after the professor participated in a faculty development course, Engineering Education Theory and Practice, at the Fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This insight can guide instructional designers to create more dynamic and multifaceted learning experiences. Pinto and Zvacek (2022) found that a T-shaped design positively impacted learning, fostering teamwork and discussion. Educators can incorporate interdisciplinary approaches to encourage students to explore diverse subject matter, fostering well-rounded learning experiences.…”
Section: Enhanced Motivation and Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…This insight can guide instructional designers to create more dynamic and multifaceted learning experiences. Pinto and Zvacek (2022) found that a T-shaped design positively impacted learning, fostering teamwork and discussion. Educators can incorporate interdisciplinary approaches to encourage students to explore diverse subject matter, fostering well-rounded learning experiences.…”
Section: Enhanced Motivation and Engagementmentioning
confidence: 99%
“…This approach fosters engagement and a deeper understanding of the content. Cognitivist and constructivist learning theories and cognitive apprenticeship instructional model (CA) (Pinto & Zvacek, 2022) emphasize knowledge construction and active participation. By integrating these theories, IDMs promote student-centered learning and problem-solving.…”
Section: How Have Idms Integrated Principles and Concepts From Variou...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the learning effects of junior high school and university students could be improved. The authors of [36] investigated students' perspectives concerning a curricular unit that was reconstructed according to cognitivist and constructivist learning theories, the cognitive apprenticeship instructional model, and a T-shaped design. The authors of [37] proposed an artificial agent created by virtual reality, which can be used to foster a situated learning experience in an oral presentation.…”
Section: Catmentioning
confidence: 99%
“…Graduates nowadays must have both discipline-specific competencies (knowledge, skills, and disposition) (ACM and IEEE 2021) while having a solid foundation in soft skills such as communication, management, leadership, and problem-solving (Aničić et al 2017). There are various strategies to achieve the required competency and soft skills, which primarily focus on curriculum and pedagogical approaches (Boehm and Mobasser 2015;Babatope et al 2020;Pinto and Zvacek 2020;Papa et al 2021). However, students' clubs, organizations, or societies, which are apparent in an undergraduate program, also has potential to shape students' competency (King 2019).…”
Section: Introductionmentioning
confidence: 99%